Research Paper: Improving the Performance of Kaolin in Adsorbing Air Pollutant Gases using Surface Treatment by Argon Atmospheric Pressure Plasma Jet - ّFateme Aref; Rahele Aboltaman; Mehran Shahmansouri (فیزیک کاربردی ایران)
In this research, among the types of adsorbents known in nature, Kaolin was used as an adsorbent material due to its unique characteristics and special capabilities in the absorption stages. Atmospheric pressure was irradiated and after testing by a gas analyzer, we saw an improvement in the absorption performance of CO and CO2 gases in this type of adsorbent material. The effect of the output power and flow of argon gas and the duration of plasma irradiation on the properties of Kaolin was also investigated. XRD and FTIR analyses were used as characterization methods to determine the purity of Kaolin before and after irradiation, and a gas analyzer was used to analyze the obtained results. The findings of this research provide a new way to control and reduce air pollutants in cities where air pollution is one of the biological problems. In addition, the achievements of this research can lead to the expansion and effective progress in reducing the costs related to the control of pollutants and also bring reassurance in terms of biocompatibility.